An Evaluation of Mental Health Professionals’ Confidence in Performing Perinatal Assessments & The Need for the Development of an Assessment Tool - A. Delvi; L. Blake; A. Lapraik; G. Lewis (European Psychiatry, 2022)
Introduction Clinicians often do not have experience assessing perinatal patients unless they work as part of a perinatal team. Informal feedback points to a lack of confidence in performing perinatal assessments.